Heritage on a plate: investigating the antecedents of intention to sustain Malaysian heritage food among young adults - Ali Munauwar, Aida Najihah; Mohd Zaki Al-Hassan, Iman Aqhar; Bashir, Muhammad ‘Arif Aizat (Universiti Teknologi MARA, Terengganu, 2025)
Malaysia’s rich culinary heritage in today’s realm faces challenges in sustainability due to globalisation, urbanisation, and changing lifestyles, particularly among young adults. As traditional food practices gradually decline, understanding the factors influencing young Malaysians’ intention to sustain heritage food becomes crucial. This study investigates the role of social media influence, accessibility, and knowledge in shaping young adults’ intention to preserve Malaysian heritage food. Using a quantitative research approach, data were collected through surveys from young adults aged 18–25, with a total of 142 respondents. The study employed descriptive and regression analyses to examine the relationships between the identified factors and their impact on the intention to sustain heritage food. Findings reveal that social media and knowledge significantly influence young adults’ commitment to heritage food sustainability, whereas accessibility alone does not strongly impact their intention. The study highlights the growing role of digital platforms in promoting culinary heritage by enhancing awareness, fostering engagement, and facilitating knowledge transmission. Additionally, it underscores the importance of cultural education in strengthening young adults’ appreciation and willingness to sustain traditional food practices. These findings provide valuable insights for policymakers, educators, and cultural institutions to develop targeted strategies for preserving Malaysia’s gastronomic heritage. Future efforts should focus on integrating digital engagement with educational initiatives to ensure the continued relevance of heritage food in contemporary society. By addressing key determinants of heritage food sustainability, this study contributes to the broader discourse on cultural preservation and offers practical recommendations for fostering Malaysia’s culinary legacy among younger generations.